(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The current research aimed to identify the role of using artificial intelligence (AI) applications in improving the job performance of secondary school mathematics teachers from their perspective. The study also aimed to identify the most frequently used applications by teachers. A descriptive-analytical approach was used, and a questionnaire consisting of 20 items was developed and administered to a sample of 175 mathematics teachers. The results showed that the role of using AI applications in improving the job performance of secondary school mathematics teachers, from their perspective, was significant. The most frequently used AI application by mathematics teachers in teaching mathematics was ChatGPT, while Bing AI was the least used. There was no statistically significant difference between the mean scores of the sample on the questionnaire regarding the role of using AI applications in improving the job performance of secondary school mathematics teachers, based on the gender variable. However, there was a statistically significant difference based on the educational qualification variable, favoring those with postgraduate degrees; based on the number of years of experience variable, favoring those with less than 10 years; and based on the training courses in the field of AI, favoring those who had completed training courses.